Auch an der Universität - Über den Beginn von Entrechtung und Vertreibung vor 80 Jahren. Reden der Zentralen Gedenkveranstaltung der Universität Hamburg im Rahmen der Reihe ,,Hamburg erinnert sich 2013 am 8. April 2013" - Nicolaysen, Rainer (Hamburger Universitätsreden Neue Folge, 2014)
2013 was the 80th year of the takeover of power by the National Socialists in 1933, the 75th year of the Reichspogromnacht" on 9 November 193, and the 70th year of the air raids on Hamburg by allied groups known as ""Operation Gomorrha"" in the summer of 1943. With the slogan ""Hamburg remembers 2013"", a large number of commemoration ceremonies were held. The University of Hamburg was involved in the program of events during the commemorative year through several of its institutions. For its central event, it chose the reference date of 7 April 1933, the day on which the ""Law on the Restoration of Professional Officials"" came into force - the basis for the dismissals of ""non-Aryan"" and politically undesirable university teachers in Germany. This volume brings together the four speeches given at the event on 8 April 2013. The commemoration ceremony on April 8,2013 and its documentation are part of a thirty-year-long intensive engagement of the University of Hamburg with its history in the ""Third Reich"" - a confrontation that has to be continued and revived over and over again over the course of generations."